2016
DOI: 10.1039/c5gc02231b
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-compression molding of chitosan with a deep eutectic mixture for biofilms development

Abstract: A deep eutectic mixture of choline chloride and citric acid was used for the preparation of chitosan bio-films by thermo-compression molding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 29 publications
0
29
1
1
Order By: Relevance
“…[1][2][3] Due to its low cost, easy lm-forming capacity, environmental friendliness, alkali stability, biodegradability, excellent mechanical properties and thermal stability, it is very valuable in the preparation of membranes, and has attracted great research interest. [4][5][6][7] Many studies have reported that chitosan has an excellent ability to form microspheres, membranes and bers, which gives it a signicant advantage over other absorbable membrane materials in the design of packaging structures. 8 However, chitosan is generally prepared using acetic acid as solventa method that brings a number of disadvantages, such as minimal thickness, peculiar smell and fragile nature of the lms at low concentration of chitosan, as well as easy drying and curl.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Due to its low cost, easy lm-forming capacity, environmental friendliness, alkali stability, biodegradability, excellent mechanical properties and thermal stability, it is very valuable in the preparation of membranes, and has attracted great research interest. [4][5][6][7] Many studies have reported that chitosan has an excellent ability to form microspheres, membranes and bers, which gives it a signicant advantage over other absorbable membrane materials in the design of packaging structures. 8 However, chitosan is generally prepared using acetic acid as solventa method that brings a number of disadvantages, such as minimal thickness, peculiar smell and fragile nature of the lms at low concentration of chitosan, as well as easy drying and curl.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan can be also processed using DES. Galvis-Sánchez et al (2016) [111] prepared thermocompression molded films with chitosan (deacetylation degree 90%), CC, and citric acid (CA) (molar ratio 1:1). CC and CA were added separately to chitosan (not as a liquid mixture), and this three components system was heated for 30 min at 70 • C and then 3% acetic acid solution was added, and the formed paste was hot-pressed at 120 • C. In comparison to chitosan/CA films, chitosan/CC/CA ones exhibited higher water sorption ability.…”
Section: Novel Green Solvents As Plasticizers For Thermomechanical Trmentioning
confidence: 99%
“…Finally, DESs have been used for chitosan processing. Galvis-Sánchez et al [ 282 ] prepared thermocompression molded films with chitosan (DA 90%), using [Ch]Cl:CA (1:1). SEM and XRD analysis revealed that acetic acid interacted with CA and promoted the reorganization of chitosan molecules and their amorphization, which in turn resulted in an increase in the elongation at break of the films.…”
Section: Chitinmentioning
confidence: 99%